'The burglar's mate'? How London's probation officers persuaded magistrates in Social Enquiry Reports, 1958-72 - Lunan, J (2014)
A clash of generations occurred in the 1960s Probation Service when increasing numbers of university graduates entered the profession. They have been described as permissive by historians because they prioritised the welfare of the offender. This was in contrast to their older, and relatively untrained, colleagues for whom a reform project was premised on the disciplining of character. Due to a lack of sources, however, it remains unclear how these two generations differed in their attempts to persuade magistrates over sentencing outcomes. Fortuitously, a rare cache of over 2,000 Social Enquiry Reports (SERs) survives in the records of the City’s Justice Rooms. Written by probation officers from across the Metropolitan London area, the reports represent a cross section of the capital’s diverse population. Using a number of techniques including oral and secondary sources, this thesis identifies members of both generations and examines the way that they persuaded magistrates. Sorting the SERs into types of offender, the thesis shows that both generations ultimately persuaded magistrates by subtly indicating in reports whether or not the offender and their families conformed to conventional gender norms. The main reason why SERs by the permissive university graduates closely resembled those written by their older colleagues was due to their common perception of magistrates as being socially conservative. Regardless of how liberal or not Britain became in the sixties, the courtroom was not considered to be a place where a rethink of morality had occurred. The university graduates therefore invoked normative character ideals in SERs because they believed it was likely to be the best way to achieve the desired outcome in court. Finally, as responses to offending were shaped by gender ideologies rather than the nature of the offence or previous convictions, the concept of the probation officer as ‘the burglar’s mate’ is rendered problematic.